Gain-of-Function Mutations in KCNN3 Encoding the Small-Conductance Ca2+-Activated K+ Channel SK3 Cause Zimmermann-Laband Syndrome - Bauer, Christiane K.; Schneeberger, Pauline E.; Kortüm, Fanny; Altmüller, Janine; Santos-Simarro, Fernando; Baker, Laura; Keller-Ramey, Jennifer; White, Susan M.; Campeau, Philippe M.; Gripp, Karen W.; Kutsche, Kerstin (American journal of human genetics, 2019)
Zimmermann-Laband syndrome (ZLS) is characterized by coarse facial features with gingival enlargement, intellectual disability (ID), hypertrichosis, and hypoplasia or aplasia of nails and terminal phalanges. De novo missense mutations in KCNH1 and KCNK4, encoding K+ channels, have been identified in subjects with ZLS and ZLS-like phenotype, respectively. We report de novo missense variants in KCNN3 in three individuals with typical clinical features of ZLS. KCNN3 (SK3/KCa2.3) constitutes one of three members of the small-conductance Ca2+-activated K+ (SK) channels that are part of a multiprotein complex consisting of the pore-forming channel subunits, the constitutively bound Ca2+ sensor calmodulin, protein kinase CK2, and protein phosphatase 2A. CK2 modulates Ca2+ sensitivity of the channels by phosphorylating SK-bound calmodulin. Patch-clamp whole-cell recordings of KCNN3 channel-expressing CHO cells demonstrated that disease-associated mutations result in gain of function of the mutant channels, characterized by increased Ca2+ sensitivity leading to faster and more complete activation of KCNN3 mutant channels. Pretreatment of cells with the CK2 inhibitor 4,5,6,7-tetrabromobenzotriazole revealed basal inhibition of wild-type and mutant KCNN3 channels by CK2. Analogous experiments with the KCNN3 p.Val450Leu mutant previously identified in a family with portal hypertension indicated basal constitutive channel activity and thus a different gain-of-function mechanism compared to the ZLS-associated mutant channels. With the report on de novo KCNK4 mutations in subjects with facial dysmorphism, hypertrichosis, epilepsy, ID, and gingival overgrowth, we propose to combine the phenotypes caused by mutations in KCNH1, KCNK4, and KCNN3 in a group of neurological potassium channelopathies caused by an increase in K+ conductance.